2016
DOI: 10.1371/journal.pone.0165725
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of High VEGF-C Expression for Patients with Breast Cancer: An Update Meta Analysis

Abstract: BackgroundThe prognostic significance of vascular endothelial growth factor C (VEGF-C) expression in breast cancer (BC) patients remains controversial. Therefore, this meta-analysis was performed to determine the prognostic significance of VEGF-C expression in BC patients.Materials and MethodsSeveral electronic databases were searched from January 1991 to August 2016. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to evaluate the prognostic significance of VEGF-C expression f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
12
1
1
Order By: Relevance
“…A number of recent meta-analyses that summarize the results of these clinical investigations preferentially indicate positive VEGFC/D and VEGFR3 immunostaining in tumor cells and a positive correlation between the expression level and lymph node involvement or disease progression (48,49). Similar data were obtained for breast, colorectal and esophageal cancer patients (50)(51)(52). However, in all the reports, significant discrepancies across particular studies have been highlighted.…”
Section: Discussionmentioning
confidence: 73%
“…A number of recent meta-analyses that summarize the results of these clinical investigations preferentially indicate positive VEGFC/D and VEGFR3 immunostaining in tumor cells and a positive correlation between the expression level and lymph node involvement or disease progression (48,49). Similar data were obtained for breast, colorectal and esophageal cancer patients (50)(51)(52). However, in all the reports, significant discrepancies across particular studies have been highlighted.…”
Section: Discussionmentioning
confidence: 73%
“…The contradiction among the original studies, as well as among some interesting recent meta-analyses[ 43 44 ], concerning the prognostic significance of most of the angiogenesis-related proteins has hindered their clinical utility in breast cancer patients. One has to remember however, that in most of the existing studies, including ours, the findings are not purely prognostic, since most if not all studies included some type of treatment (hormonal treatment or chemotherapy).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-C expression in tumor tissue has been evaluated immunohistochemically in many studies, but the results have not been consistent [ 14 ]. However, a recent meta-analysis that included 21 studies and 2828 patients with breast cancer reported HRs of 1.87 (95% CI 1.25–2.79, p = 0.001) for RFS and 1.96 (95% CI 1.15–3.31, p = 0.001) for OS for patients with high tumor VEGF-C expression [ 5 ]. More recent studies have confirmed the negative prognostic role of VEGF-C based on its mRNA levels in tumor tissue [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, greater expression of VEGF-C (measured by immunohistochemistry in tumor biopsies) is related to poorer relapse-free survival (RFS) and overall survival (OS). A recent meta-analysis that included 21 studies and 2828 patients with breast cancer reported hazard ratios (HRs) of 1.87 (95% confidence interval [CI] 1.25–2.79, p = 0.001) for RFS and 1.96 (95% CI 1.15–3.31, p = 0.001) for OS in patients with high tumor VEGF-C expression [ 5 ]. However, the cut-off values used to define high tumor VEGF-C expression varied considerably among the studies.…”
Section: Introductionmentioning
confidence: 99%